Peran Teknologi Di Dalam Memoderasi Pengaruh Internal Networking Terhadap Kinerja Usaha Industri Kecil dan Menengah Pada Saat Pendemi Covid-19 - Satria Tirtayasa; Hazmanan Khair; Januri Januri (University of Merdeka Malang, 2021)
The purpose of this research is to analyse the Effect of Technology as moderator variable Throught the relationship of Internal Networking (production and distribution) with SME’s business performance. This study have been done in Covid-19 Pendemy at Medan City. The unit of analysis of this research is Small Medium Industry (IKM) company, where those company located in one area (cluster Small Medium Industry ). The population of this research are 103 IKM and the sample are 103 IKM (census).Data collection was used questionnaire, where the respondent are the owner of the IKM company. The questionnaire response was high where 3 owner rejected to made responsed (rejeccted), thus this research have 100 questionnaires reponses. The analysis method was using Hierarchi Regression and process analysis was used SPPS. The results of the research showed that the production and distribution have positive and significant effect with IKM performance. The effect of technology as moderator effect was found that negative and significant influence the relationship production and distribution with IKM performance. Thus, the effect of technology as moderator variable in pendemic Covid-19 was not dominant, because of the IKM compay faced decreased demand and indeed influence of Sales Margin.